Wednesday

April 16, 2014

April 16, 2014

Posted by **Dan** on Sunday, November 9, 2008 at 9:20pm.

f(x) = (2x+5)/(x^2-3)

f'(x)= (2)*(x^2 -3)-(2x+5)*2x/(x^2-3)^2

is that correct???

f(x)= (lnx)(cos x)

f'(x)= 1/x*-sinx

or do i have to use the product rule??

thank you.

- CALC -
**bobpursley**, Sunday, November 9, 2008 at 9:54pmf'(x)= (2)/(x^2 -3)-(2x+5)*2x/(x^2-3)^2

see the first term.

next one

use the product rule.

**Related Questions**

calculus - find the following derivatives: f(x) = (2x+5)/(x^2-3) f'(x)= (2)*(x^2...

College Calc - Problem: y=sqrtx ^1/x. Find DY/DX. ln(f(x))=lnx^1/2x or lnx to ...

Mathematics - Trigonometric Identities - Reiny - Mathematics - Trigonometric ...

Calculus - I don't know if I did these problems correctly. Can you check them? ...

math - the problem is 2cos^2x + sinx-1=0 the directions are to "use an identity ...

Mathematics - Trigonometric Identities - Prove: sin^2x - sin^4x = cos^2x - cos^...

Trig - Simplify sin x cos^2x-sinx Here's my book's explanation which I don't ...

Math (trigonometric identities) - I was given 21 questions for homework and I ...

Trig....... - I need to prove that the following is true. Thanks (2tanx /1-tan^x...

Trig Help - Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx...